2012
DOI: 10.5551/jat.10249
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Bacteria Promote Macrophage Foam Cell Formation Via Toll-Like Receptor-Dependent Lipid Body Biosynthesis

Abstract: Conclusions:The bacterial debris observed in human atheroma, which is currently considered to be harmless, may have potential to contribute to disease progression via TLR-dependent lipid body formation in macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 48 publications
1
48
0
1
Order By: Relevance
“…TLR1/2 and TLR4 agonists stimulate lipid body formation in the presence and absence of lipoprotein supplementation (33). The ability of TLR agonists to prolong TAG retention, in addition to augmenting the uptake of oxidized LDL (and promoting desmosterol synthesis (34)), suggests that both phenomena may contribute to the formation of macrophage foam cells in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…TLR1/2 and TLR4 agonists stimulate lipid body formation in the presence and absence of lipoprotein supplementation (33). The ability of TLR agonists to prolong TAG retention, in addition to augmenting the uptake of oxidized LDL (and promoting desmosterol synthesis (34)), suggests that both phenomena may contribute to the formation of macrophage foam cells in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Diverse bacteria promote formation of foam cells from macrophages by lipid body biosynthesis that is dependent upon toll-like receptors (226). In this study, foam cell formation cannot be caused by phagocytosis of oxidized LDL by the scavenger receptor, since neither inhibition of LDL oxidation nor inhibition of the scavenger receptor are able to prevent foam cell formation by bacteria.…”
Section: Homocysteine Inflammation Infection and Atherogenesismentioning
confidence: 75%
“…A recent study found that exposure to a wide variety of bacteria commonly found in human atherosclerotic plaques induced lipid body formation and cholesterol ester accumulation in murine macrophages. 119 Furthermore, this effect was found to occur in a Toll-like receptor (TLR) 2 and/or TLR 4 dependent manner, giving rise to the possibility that debris from non-viable bacteria within macrophages may promote foam cell formation by interacting with TLRs. Thus exposure to the microbial components of respiratory pathogens may provide a more extreme example of the microbial priming for plaque progression provided by the oral and gut commensals.…”
Section: Localised Vascular Inflammationmentioning
confidence: 97%
“…119 Aside from potential direct infection of plaques, the finding of bacterial debris in human plaques may be the result of recruitment to the plaque of inflammatory cells that have already encountered micro-organisms in the lung or other remote locations, leading to increased localised inflammation and atherosclerosis progression. A recent study found that exposure to a wide variety of bacteria commonly found in human atherosclerotic plaques induced lipid body formation and cholesterol ester accumulation in murine macrophages.…”
Section: Localised Vascular Inflammationmentioning
confidence: 99%